Secular teachers in Jewish religious schools: passing, resistance, and freedom of religion. (4th July 2021) - Perry-Hazan, Lotem; Finefter-Rosenbluh, Ilana; Muzikovskaya, Elizabeth
ABSTRACT: This study explored the perceptions of 25 secular teachers employed in American, Australian, and Israeli Jewish religious schools regarding disparities between their secular identity and their school's religious habitus. It also examined the ways these teachers cope with such disparities. Findings suggest that teachers' challenges were anchored in their freedom of religion and conscience, educational credo, and framed organisational position. However, the teachers acknowledged student benefits such as students' exposure to diversity and support offered to those experiencing religious and identity conflict. Identified patterns of teachers' coping strategies included opposition, adaptation, and fence-sitting . We drew upon the literature on passing and everyday forms of resistance in schools having rigid public transcripts to explain these strategies' moral and emotional costs. The study's implications apply to other religious schools and educational settings characterised by rigid public transcripts of discipline and accountability policies that may conflict with teachers' identity and educational credo.